Optimization of Ellagic Acid Purification from Pomegranate Husk by Antisolvent Recrystallization. Issue 6 (2nd May 2018) - Wang, Li; Lian, Bolin; Wu, Weiwei; Deng, Yiping; Liu, Yanjie; Wang, Lingling; Li, Yuanyuan; Wang, Zijian; Zhao, Xiuhua
Abstract: Ellagic acid (EA) was produced from pomegranate husk by extraction of tannins followed by acid hydrolysis and purified by antisolvent recrystallization. Response surface methodology, based on a five‐level, four‐variable central composite design, was employed to find the optimum purification conditions. Under these conditions, high purity and yield of EA was obtained in close agreement with the predicted values by the model. Analyzes of surface morphology and in vitro percutaneous absorption experiments of EA let conclude that the granule morphology of the purified EA was significantly different from the crude EA, and its particle size was much smaller than that of the crude EA. Evaluation in vitro demonstrated that the permeation rate of the purified EA was higher compared with the crude EA. Abstract : Despite significant medicinal value, pomegranate husk containing valuable ellagic acid is mostly disposed. Crude ellagic acid was produced from pomegranate husk by extraction of tannins followed by acid hydrolysis and further purification by antisolvent recrystallization. Response surface methodology helped to find the optimum purification conditions for obtaining high‐purity ellagic acid.